2019
DOI: 10.22235/cp.v13i2.1883
|View full text |Cite
|
Sign up to set email alerts
|

Factores asociados a los accidentes de motocicleta en Barcelona, España

Abstract: Este estudio analizó los accidentes de motocicleta y ciclomotor en Barcelona (España). 53.190 informes de conductores de motocicleta y ciclomotor involucrados en accidentes entre los años 2006 y 2011 fueron extraídos de la base de datos de accidentes con víctimas de la Dirección General de Tráfico. Estos datos fueron analizados en términos de sexo, grupos de edad, motivo del desplazamiento, día de la semana, infracciones de velocidad, uso del casco y lesividad, con el objetivo de estudiar las características d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…On the other hand, encouraging modal change from cars and motorcycles to micromobility modes would result in an overall reduction in emissions, even with the current state of micromobility technology. That solution would be particularly promising in cities with a high share of private transport use, or in cities such as Barcelona where motorbikes represent a large share of private mobility [60,61]. Ultimately, the more sustainable and healthier way to integrate these new micromobility services could be to make them complement public transportation grids [62], and to tailor their use towards mid-distance trips.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, encouraging modal change from cars and motorcycles to micromobility modes would result in an overall reduction in emissions, even with the current state of micromobility technology. That solution would be particularly promising in cities with a high share of private transport use, or in cities such as Barcelona where motorbikes represent a large share of private mobility [60,61]. Ultimately, the more sustainable and healthier way to integrate these new micromobility services could be to make them complement public transportation grids [62], and to tailor their use towards mid-distance trips.…”
Section: Discussionmentioning
confidence: 99%
“…Motorcycle popularization and affordability has increased in the last years, and acquisition focus and use purposes of small or big engine potency differs both in user profile and in marketing (Marim, 2010). It is believed and demonstrated that motorcycles with bigger engine potency can present differences in accident profile compared to small engine potency (Langley et al, 2000;Waseem et al, 2019;Hidalgo-Fuentes & Sospedra-Baeza, 2019;Méndez-Magaña et al, 2019), which can provide subsidies for specific health policies.…”
Section: Introductionmentioning
confidence: 99%
“…55 años y 2018 de 34,86 años, estado civil soltero y un nivel académico por lo menos de secundaria o educación media (ver tabla 1). Estos hallazgos son coincidentes con los reportados por estudios precedentes(13 -20); a este respecto, Hidalgo et al(21) sostienen que existe una relación directa entre la accidentalidad y factores sociodemográficos como ser hombre, ser joven y soltero. Los hombres tienden a usar más la motocicleta como medio de transporte para el cumplimiento de actividades laborales y sociales, además, suelen conducir a mayor velocidad y bajo el efecto de sustancias psicoactivas o alcohol(22,23).…”
unclassified